2018
DOI: 10.1200/cci.18.00013
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits and Challenges of Using Patient Decision Aids to Support Shared Decision Making in Health Care

Abstract: Shared decision making (SDM) and patient-centered care require patients to actively participate in the decision-making process. Yet with the increasing number and complexity of cancer treatment options, it can be a challenge for patients to evaluate clinical information and make risk–benefit trade-offs to choose the most appropriate treatment. Clinicians face time constraints and communication challenges, which can further hamper the SDM process. In this article, we review patient decision aids (PDAs) as a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 61 publications
0
64
0
Order By: Relevance
“…Medical science and practice has started acknowledging this challenge and has developed several important advances to improve patient-oriented clinical decision-making. This includes, for example, the increased use of patient-reported outcomes [17,18,52], which have been shown to increase the implementation of shared decision-making and can serve as a basis for clinical decision support systems [53]. Another approach that has been shown to improve decision-making is the use of patient decision aids [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical science and practice has started acknowledging this challenge and has developed several important advances to improve patient-oriented clinical decision-making. This includes, for example, the increased use of patient-reported outcomes [17,18,52], which have been shown to increase the implementation of shared decision-making and can serve as a basis for clinical decision support systems [53]. Another approach that has been shown to improve decision-making is the use of patient decision aids [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…In theory, this sounds significantly better than the previous approach, yet it "as-sumes that patients are capable of taking in complex information from health care providers at a most vulnerable time in their lives and then synthesizing that information to make rational treatment choices" [13]. The complexity of information involved in oncological decision-making has led to the implementation of decision aids in oncology [17]. While their dissemination is still limited, multiple trials have demonstrated positive impacts on the decision-making process.…”
Section: Shared Decision-making In Oncologymentioning
confidence: 99%
“…While there is a dearth of PDAs for solving ethical dilemmas, their absence does not preclude the use of decision science, which, as we show, goes beyond aids to encompass the various factors that affect decision-making processes and the science of how human beings make choices. 1,2,3…”
Section: Commentarymentioning
confidence: 99%
“…3 Action bias, the desire to do something-perhaps anything-to decrease anxiety, could lead to a hasty or poorly considered decision. 2,3 In pediatric cases, parents could be viewed as a single unit rather than as individuals. While both parents commonly want to do what is best for their child, it is important to acknowledge that each parent might process information differently and bring unique perspectives and narratives to the decision-making process, which in turn could influence their experience of grief.…”
Section: Emotions and Decision Makingmentioning
confidence: 99%
See 1 more Smart Citation